Application of Analytical Hierarchy Process (AHP) Methods in Decision Making of Lecturer Performance Determination on the Utilization of Online Learning in Polytechnic Media Kreatif - Tri Fajar Yurmama Supiyanti; Herly Nurrahmi; Muhammad Suhaili (Budapest International Research and Critics University, 2021)
In the development of technology, decision making is something that will be done by all humans in life. Making a decision is not an easy matter because every decision made and carried out by someone must consider a risk to be borne. Decision Support System (DSS) is a system which utilizes the use of computers in every decision-making process. The achievement of the learning objectives that have been set or have just been achieved depends on the ability of human resources (lecturers) in carrying out their duties. To be able to recognize the ability and potential of a lecturer for his work, a university must have an assessment system to support decisions in determining the performance of a lecturer. The purpose of this research is to obtain a method that has a high accuracy value with the analytical hierarchy process (AHP) method so that a high accuracy and fast method is obtained to determine the performance of lecturers in the use of online learning. The result of this research is obtained criteria to produce a solution in determining the performance of lecturers such as criteria, attendance, performance, opportunity, and integrity.